On the focus-sensitive presupposition triggers "too, again, also, even" - Abrusán, Márta (Proceedings of Sinn und Bedeutung, 2019)
This paper proposes to derive the presupposition of additive particles too, as well, also and the temporal particle again. It argues that the presuppositions of these particles can be predicted by the same presupposition triggering mechanism that was proposed for so-called soft triggers in Abrusán (2011). It is shown that presupposition suspension facts, characteristic of soft triggers, do not arise with additive particles because of their anaphoric and focus-sensitive nature. Finally, the paper proposes that the soft-hard presupposition distinction can be explained not in terms of differences in the nature of the presupposition but rather as a consequence of the anaphoric/focus-sensitive nature of various triggers.